# How do I factor the polynomial x^5-4x^3-8x^2+32 completely?

### 2 Answers | Add Yours

We have to factor x^5 - 4x^3 - 8x^2 + 32

x^5 - 4x^3 - 8x^2 + 32

=> x^3( x^2 - 4) - 8(x^2 - 4)

factor out x^2 - 4

=> (x^2 - 4)(x^3 - 8)

use the relation a^2 - b^2 = (a - b)(a + b)

=> (x - 2)(x + 2)(x^3 - 8)

use a^3 - b^3 = (a - b)(a^2 + ab + b^2)

=> (x - 2)(x + 2)(x - 2)(x^2 + 2x + 4)

=> (x - 2)^2*(x + 2)(x^2 + 2x + 4)

**The required factorization of the polynomial is (x - 2)^2*(x + 2)(x^2 + 2x + 4)**

I'll suggest to group the 1st term with the last one.

We'll use the formula:

a^n + b^n = (a+b)(a^n-1 - a^n-2*b + ... + b^n)

x^5 + 32 = x^5 + 2^5 = (x+2)(x^4 - 2x^3 + 4x^2 - 8x + 16)

We'll group the middle terms:

-4x^3-8x^2 = -4x^2(x + 2)

We'll re-write the polynomial:

(x+2)(x^4 + 2x^3 + 4x^2 + 8x + 16) - 4x^2(x + 2)

We'll factorize by x+2:

(x+2)(x^4 - 2x^3 + 4x^2 - 8x + 16 - 4x^2)

(x+2)(x^4 - 2x^3 - 8x + 16)

We'll regroup x^4 - 2x^3 = x^3(x-2)

-8x + 16 = -8(x-2)

(x+2)(x^3(x-2) - 8(x-2)) = (x+2)*(x-2)*(x^3 - 8)

But x^3 - 8 = (x-2)(x^2 + 2x + 4)

The polynomial will become:

(x+2)*(x-2)*(x^3 - 8) = (x+2)*(x-2)^2*[(x^2 + 2x + 4)]

(x+2)*(x-2)*(x^3 - 8) = (x-2)*(x^2 - 4)*(x^2 + 2x + 4)

**The factorized polynomial is (x-2)*(x^2 - 4)*(x^2 + 2x + 4).**